2019
DOI: 10.1002/jrs.5653
|View full text |Cite
|
Sign up to set email alerts
|

A joint experimental and theoretical Raman study on the interactions of pyridine adsorbed on chemically pure Ag18 clusters

Abstract: The interaction of pyridine–Ag has been a hot topic since the finding of surface‐enhanced Raman scattering; however, there is still challenge to accurately evaluate the interactions within nano‐systems. Here we have synthesized chemically pure Ag18 nanoclusters by a facile method based on laser ablation in liquid and conducted a joint experimental and theoretical Raman spectroscopic study for pyridine adsorbed on the specific‐sized Ag clusters. As a result, altered Raman feature for the pyridine‐Ag18 system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…An et al [ 27 ] reported a joint experimental and theoretical Raman study of the interactions of pyridine adsorbed on chemically pure Ag 18 clusters. They found that a comprehensive and semiquantitative study provides firm evidence for the chemical enhancement mechanism in SERS theory.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…An et al [ 27 ] reported a joint experimental and theoretical Raman study of the interactions of pyridine adsorbed on chemically pure Ag 18 clusters. They found that a comprehensive and semiquantitative study provides firm evidence for the chemical enhancement mechanism in SERS theory.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…In recent decades, extensive coinage metal clusters have been successfully synthesized via wet chemistry by proper ligand protection, including the aforementioned Au 20 , , Au 13 , and Au 18 nanoclusters . Meanwhile, a few ligand-protected Ag n nanoclusters of similar sizes have also been synthesized, such as Ag 18 , and Ag 19 nanoclusters . The extensive reports of coinage metal clusters allow their catalytic and optical properties to be revealed; however, the precise atomistic mechanism relating to activity and stability is still elusive and awaits full understanding.…”
mentioning
confidence: 99%